(untitled) (ItalianoLinguadue, 2025)
I due episodi biblici di Babele e di Pentecoste vengono considerati fondamenti simbolico-metaforici delle politiche linguistiche dato che entrambi sono basati sull’idea del riconoscimento e del valore positivo della diversità linguistica. L’idea della loro complementarità non anima solo le interpretazioni filosofico-linguistiche, ma anche le rappresentazioni visive dei due episodi. Tra le rappresentazioni artistiche contemporanee viene esaminata quella di Andrea Mastrovito presso il Foyer Catholique Européen, dove il dono dello Spirito nelle lingue del mondo è il simbolo del percorso verso il senso, nel dialogo che anima l’incontro fra le persone e fra le lingue del mondo. Between Babel and Pentecost. theories and visual representations for a politics of multilingualism The two biblical episodes of Babel and Pentecost are regarded as symbolic-metaphorical foundations of language policies since both are based on the idea of the recognition and positive value of linguistic diversity. The idea of their complementarity not only animates philosophical-linguistic interpretations, but also the visual representations of the two episodes. Among the contemporary artistic representations, the one by Andrea Mastrovito at the Foyer Catholique Européen is examined, where the gift of the Spirit in the languages of the world is the symbol of the path towards meaning, in the dialogue that animates the encounter between people and between the languages of the world.